Analisis lokasi titik rawan kecelakaan (black spot) pada Ruas Jalan Raya Labuan (KM 1 – KM 10) Pandeglang - Banten - Muhammad Apriansyah; Muhammad Oka Mahendra (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2025)
The number of traffic accidents in Indonesia continues to increase every year, which contributes to the increasing death rate among the population. Similar conditions occurred in Pandeglang Regency, especially on the Labuan highway from KM 1 to KM 10, which experienced an increase in the number of accidents as seen from the LAKA (Traffic Accident) data from the Pandeglang Police from 2020 - 2024, both for Deaths (MD), Serious Injuries (LB) and Minor Injuries (LR). This study aims to identify the location of accident-prone points (black spots) along KM 1 - KM 10 of the Labuan highway, Pandeglang Regency and analyze the causal factors and solutions to the problems caused by black spots along KM 1 - KM 10 of the Labuan highway, Pandeglang Regency. The method used is to use primary data and secondary data. For data analysis using the Accident Rate and Equivalent Accident Number (EAN) methods with the use of limit values using the Final Control Limit (BKA) method and the Upper Control Limit (UCL) method. The results of the study show that: 1.) The number of traffic accidents on the Labuan Highway, Pandeglang Regency throughout 2020 - 2024 fluctuated; 2.) Location of accident-prone points (black spots) on the KM 1 - KM 3 segment, with EAN values exceeding the Upper Control Limit (BKA) and Upper Control Limit (UCL) values; 3.) The dominant factors causing accidents on Jalan Raya Labuan, Pandeglang Regency, especially on the KM 1 - KM 3 segment, include minimal street lighting, sharp bends, lack of traffic signs, and extreme road contours; and 4.) The solution includes repair and maintenance of street lighting, installation of speed limit signs and reflectors, construction of rumble strips, and installation of accident-prone warning signs and warning lights. It is hoped that this solution can become the basis for targeted special handling to prevent and reduce traffic accidents in the Labuan – Pandeglang Highway area.